(untitled) (Journal of Physical Education (Maringá), 2013)
Coaches have been teaching physical skills and techniques for years but it is only relatively recently that they have started to focus on, and teach mental skills. The lack of focus is unfortunate, in that over 20 years ago Gould, Hodge, Peterson and Petlichkoff (1987) found that 82% of coaches rated mental toughness as the most important psychological attribute in determining wrestling success, although only 9% of them felt that they were successful in teaching it. However, there has been an increase in mental toughness research during the past several years that has tended to focus on the conceptualization of mental toughness specific to establishing a clearer definition of the construct.